2006
DOI: 10.1007/s10750-006-0164-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Callitriche L. clones and environmental variables using genotyping

Abstract: The genetic variation and clonality in Callitriche L. populations from 16 headwater rivers in Belgium were determined by random amplified polymorphic DNA (RAPD). It was shown that samples of morphological C. obtusangula can be separated into at least two genetically distinct groups. Both gene pools occurred within each considered river basin, i.e. Nete and Meuse. A multivariate analysis showed that the variability among different clones, as characterized by their genotypes, can be explained through ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A number of studies suggested low within-population variability due to predominance of clonal growth such as Ceratophyllum L. (Les, 1988;Kaplan & Stephanek, 2003), Zannichellia L. (Triest & Vanhecke, 1991), Potamogeton coloratus Hornem, P. pectinatus L. (also named Stuckenia pectinata (L.) Börner), P. filiformis Pers. (Hollingsworth et al, 1995(Hollingsworth et al, , 1996 and Callitriche obtusangula Le Gall (Triest & Mannaert, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies suggested low within-population variability due to predominance of clonal growth such as Ceratophyllum L. (Les, 1988;Kaplan & Stephanek, 2003), Zannichellia L. (Triest & Vanhecke, 1991), Potamogeton coloratus Hornem, P. pectinatus L. (also named Stuckenia pectinata (L.) Börner), P. filiformis Pers. (Hollingsworth et al, 1995(Hollingsworth et al, , 1996 and Callitriche obtusangula Le Gall (Triest & Mannaert, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Callitriche species exhibit considerable variation in chromosome number, ecology, life form and pollination systems (Philbrick, 1993) but identification at species level remains difficult. Various RAPD multilocus genotypes (MLGs) indicate a relationship with environmental variables (Triest & Mannaert, 2006), thereby suggesting differentiation between habitats. Z. palustris s.l.…”
Section: Introductionmentioning
confidence: 99%
“…Not much is known about the relationship between pond habitat characteristics and macrophyte gene diversity of but, e.g. in the context of a river system, a non-random distribution of Callitriche L. clones was observed in relation to alkalinity (Triest & Mannaert, 2006). Single ponds within a lagoon system can show different physical properties, salinities, inundation periods, sediment oxygenation, etc.…”
Section: Discussionmentioning
confidence: 99%